SPATIAL STUDY OF THE DISTRIBUTION OF HEALTH CENTER WORK AREAS IN IMPROVING HUMAN HEALTH DEVELOPMENT IN BENGKULU CITY - Aqilla Fadia Utari; Iswandi Umar (Universitas Sebelas Maret (UNS), 2025)
The objectives of this study are as follows: 1. To find out the area of work of health centres in Bengkulu City. 2. To find the ideal service distance between health centers in Bengkulu City using the buffer and network analyst methods. 3. To find out the policy direction of the influence of the distribution of health centre work areas on increasing the Human Development Index. The research method used is a descriptive quantitative method using a geographic information system in buffer analysis techniques, network analyst service areas, and AHP Expert Choice. The results of this study indicate 1. The area of work of Health Centers is spread across nine sub-districts, where each sub-district has 2 to 3 Health Centers that can reach and serve the entire community in Bengkulu City. 2. The facilities of Health Centers in Bengkulu City show that 13 health centers meet the ideal service distance of 2 km, and seven health centers do not meet the ideal service distance. The health center has served the entire community, as seen from the average number of residents served in each health center of 19,555. This reach can serve up to 9 work areas that health centers can accommodate. 3. Policy directions for determining the influence of the distribution of health center work areas in increasing the HDI have three policy criteria, namely accessibility, quality of health services and contribution to increasing the HDI.